Controlled Transcription of Exogenous mRNA in Platelets Using Protocells. (14th September 2015) - Chan, Vivienne; Novakowski, Stefanie K.; Law, Simon; Klein‐Bosgoed, Christa; Kastrup, Christian J.
Abstract: Transcribing exogenous RNA in eukaryotic cells requires delivering DNA to their nuclei and changing their genome. Nuclear delivery is often inefficient, limiting the potential scope of gene therapy and synthetic biology. These challenges may be overcome by techniques that allow for extranucleate transcription within eukaryotic cells. Protocells have been developed that enable transcription inside of liposomes; however, it has not yet been demonstrated whether this technology can be extended for use within eukaryotic cells. Here we show RNA‐synthesizing nanoliposomes allow transcription of exogenous RNA inside anucleate cells. To accomplish this, components of transcription were encapsulated into liposomes and delivered to platelets. These liposomes were capable of light‐induced transcription in platelets, providing proof‐of‐concept that protocell technology can be adapted for use within mammalian cells.